Artificial Intelligence-Based Visa Processing System to Reduce Paper Usage, Visa Processing Time, and Human Errors during the Application Review Process - Chollampat, Azeez (Global journal of Business and Integral Security, 2026)
Visa processing is an essential part of most international travel. However, it often entangles applicants in paperwork, requires repeated visits to visa centres, leads to long queues, and is prone to human errors. Visa applicants are often burdened by excessive paperwork, repeated visits to visa centres, long delays, and human errors. These difficulties often result in missed opportunities, frustrations and tensions. It affects a lot more vulnerable groups, such as senior citizens, pregnant women, and families, while also straining consular operations. This paper proposes an artificial intelligence (AI) based framework to transform visa processing into a faster, more reliable, and sustainable system. The proposed system integrates Optical Character Recognition (OCR), Natural Language Processing (NLP), sentiment analysis and machine learning algorithms to automate document handling, error detection, and decision support. A hybrid approach combining deep learning, language transformers, and rule-based methods is adopted to manage the complex variability in visa applications. The study also assesses the perceptions, expectations, and opinions of visa applicants and the general public about the deployment of AI in visa processing. The proposed framework aspires to deliver a digital visa processing system that is greener, more user-focused, and transparent by integrating AI into it.